Factors Affecting Quality Management of Construction Project Using Industrialized Building System: a Review - Azman, N.S.; Ramli, M. Z.; Zawawi, M. H. (International Journal of Engineering and Technology, 2018)
Quality management is essential to improve success in project implementation by using Industrialized Building System (IBS). The development of construction industry in Malaysia is encountering a relocation from ordinary techniques to a more efficient and automated strategy which is by utilizing IBS.There are a few issues in overseeing IBS construction projects which prompt low qualities such as hiring non-expertize in construction, using low quality of materials and problem with management. Therefore, this paper aim is to determine the various success factors affecting the quality management of construction project that using IBS and ranked the success factors. Found that 87 factors from review papers and two most significant factors affecting quality management in IBS are high ranked which is appointment of high experience technical team, using high quality components and materials with overall percentage 2.48% and 1.86%. However, some of the factors are repeatedly listed due to high affecting to quality.